HUBUNGAN ANTARA KADAR ETANOL, KADAR GULA REDUKSI DAN JUMLAH SEL DALAM PRODUKSI BIOETANOL DARI FERMENTASI AIR KELAPA DENGAN PENAMBAHAN PUPUK NPK - OKTANIYA OKTANIYA; FAJAR RESTUHADI; RAHMAYUNI RAHMAYUNI (Universitas Riau, 2017)
Bioethanol is an energy source that can be obtained from the fermentation of plant material. This bioethanolproduction utilizes coconut water as a fermentation medium thickened. The purpose of this study was todetermine the concentration of NPK fertilizer in the manufacture of bioethanol from coconut water bySaccharomyces cerevisiae. This study with increasing the varying NPK fertilizer concentrations of this studyconducted an experiment with four treatments and measurement in duplicate. Concentration of NPK fertilizerwere N1 (0%), N2 (1%), N3 (2%) and N4 (3%). Observations were made every 24 hours; include ethanolcontent, sugar content, pH, and the number of cells. Data were analyzed descriptively by using a tabulationand graphs. The best treatment was a combination of N4 (NPK fertilizer 3%), which produces the largestethanol 9.50%.